Functioning and disability in autism spectrum disorder: A worldwide survey of experts - de Schipper, E.; Mahdi, S.; de Vries, P.; Granlund, M.; Holtmann, M.; Karande, S.; Almodayfer, O.; Shulman, C.; Tonge, B.; Wong, V.; Zwaigenbaum, L.; Bölte, Sven (2016)
Objective: This study is the second of four to prepare International Classification of Functioning, Disability and Health (ICF; and Children and Youth version, ICF(-CY)) Core Sets for Autism Spectrum Disorder (ASD).The objective of this study was to survey the opinions and experiences of international experts on functioning and disability in ASD. Methods: Using a protocol stipulated by the World Health Organization (WHO) and monitored by the ICF Research Branch, an email-based questionnaire was circulated worldwide among ASD experts, and meaningful functional ability and disability concepts were extracted from their responses. These concepts were then linked to the ICF(-CY) by two independent researchers using a standardized linking procedure. Results: N = 225 experts from 10 different disciplines and all six WHO-regions completed the survey. Meaningful concepts from the responses were linked to 210 ICF(-CY) categories. Of these, 103 categories were considered most relevant to ASD (i.e., identified by at least 5% of the experts), of which 37 were related to Activities and Participation, 35 to Body functions, 22 to Environmental factors, and 9 to Body structures. A variety of personal characteristics and ASD-related functioning skills were provided by experts, including honesty, loyalty, attention to detail and creative talents. Reported gender differences in ASD comprised more externalizing behaviors among males and more internalizing behaviors in females. Conclusion: The ICF(-CY) categories derived from international expert opinions indicate that the impact of ASD on functioning extends far beyond core symptom domains. Autism Res 2016, 9: 959–969. © 2016 The Authors Autism Research published by Wiley Periodicals, Inc. on behalf of International Society for Autism Research.